2020
DOI: 10.31942/akses.v15i1.3360
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Minat Muzakki Membayar Zakat di Badan Amil Zakat Nasional (Baznas) Kota Semarang

Abstract: The purpose of this study was to analyze the interest of muzakki paying zakat in the Semarang baznas. The research method used is qualitative quantitative by means of distributing questionnaires. The sample used was 50 respondents. The results of this study resulted that from the independent variables (service quality, religiosity and accountability) affecting the interest of muzakki to pay zakat in Baznas Semarang only 69% of service quality, while for religiosity and accountability there was no partial effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Amil can also distribute non-cash assets directly to the rightful beneficiaries so that these assets become current assets. The assets may be consumables/long-lived goods (Muayyanah, 2019).…”
Section: Infaq and Sadaqahmentioning
confidence: 99%
“…Amil can also distribute non-cash assets directly to the rightful beneficiaries so that these assets become current assets. The assets may be consumables/long-lived goods (Muayyanah, 2019).…”
Section: Infaq and Sadaqahmentioning
confidence: 99%
“…Some researchers, e.g. Amalia and Widiastuti (2020); Ayuningtyas and Sari (2020); Yazid (2017), found that the quality of service influenced the interest of muzaki. Based on the description above, this study formulates the hypothesis that service quality affects the interest of muzaki (H3).…”
Section: Service Qualitymentioning
confidence: 99%
“…Minat membayar zakat melalui Lembaga Amil Zakat berkaitan dengan kesadaran umat Islam yang sudah memenuhi nishab dan penyalurannya diserahkan kepada Lembaga Amil Zakat tertentu (Widyarini; Wahyu Yuliana, 2019). Menurut Lucas dan Britt dalam (Ayuningtyas & Sari, 2020) Aspek minat adalah (1) Ketertarikan (interest) yang menunjukkan adanya pemusataan perhatian dan perasaan senang, (2) Keinginan (desire) ditunjukkan dengan adanya dorongan untuk ingin memiliki. (3).…”
Section: Pendahuluanunclassified